Validation of short- and long-term demographic forecasts using the Canadian Cystic Fibrosis Registry. Issue 1 (30th January 2020) - Martelli, Vanessa; Sykes, Jenna; Burgel, Pierre-Régis; Bellis, Gil; Coriati, Adèle; Stanojevic, Sanja; Stephenson, Anne Louise
National cystic fibrosis (CF) data registries track patient characteristics over time and have provided insight into both emerging trends and current clinical needs. In a recent study, Burgel et al . [1] utilised the flow method, a demographic model that predicts future trends in populations, and forecasted a 50% increase in the Western European CF population by 2025, with the adult population experiencing the largest increase. Burgel et al . [2] subsequently used the French registry to validate short-term predictions; however, the accuracy of longer term projections has not been assessed. Based on the results of this study, a model that takes into consideration changing rates over time is needed to accurately estimate future populations http://bit.ly/35IDhQ0